Inhaled levodopa in Parkinson's disease patients with OFF periods: A randomized 12-month pulmonary safety study. (February 2020) - Grosset, Donald G.; Dhall, Rohit; Gurevich, Tanya; Kassubek, Jan; Poewe, Werner H.; Rascol, Olivier; Rudzinska, Monika; Cormier, Jennifer; Sedkov, Alexander; Oh, Charles
Abstract: Introduction: CVT-301 is an orally inhaled levodopa therapy approved for the intermittent treatment of OFF episodes in Parkinson's disease patients who are taking a standard oral levodopa regimen. This open-label, randomized, controlled study over 12 months characterizes the safety, including pulmonary safety, of CVT-301 84 mg (nominal respirable levodopa fine-particle dose, 50 mg). Methods: Patients experiencing motor fluctuations were randomized 2:1 to CVT-301 or an observational cohort (OC) receiving oral standard of care. Pulmonary safety was assessed using spirometry and carbon monoxide diffusion capacity (DLCO ). Exploratory efficacy endpoints, assessed only for CVT-301, included change in Unified Parkinson's Disease Rating Scale Part III (UPDRS-III), patients achieving ON within 60 min and remaining ON at 60 min, Patient Global Impression of Change (PGIC) scale, and total daily OFF time. Results: Of 408 patients randomized, 310 completed the study (204 in CVT-301 and 106 in OC). Mean 12-month changes from baseline for CVT-301 were −0.105 L (FEV1 ) and −0.378 mL/min/mm Hg (DLCO ), and for OC were −0.117 L and −0.722 mL/min/mm Hg, respectively. Between-group comparisons were not statistically significant. For FEV1 /FVC the 12-month change was −0.3 and −1.6, respectively, which was a significant between-group difference. However, between-group differences were not significant at 3 and 9 months and all changes from baseline were small (<2.0%). UPDRS-III scores improved from predose to 60 min postdose at all assessments; 80%–85% of patients switched ON within 60 min and remained ON; and >75% reported improvement in PGIC. OFF time decreased by 1.32–1.42 h/day. Conclusion: CVT-301 84 mg induced no clinically significant differences in pulmonary function compared with the OC. Improvements in motor scores, OFF time, and patient-reported outcomes support clinical efficacy for up to 12 months. Highlights: A 12-month, open-label, randomized, controlled study of the pulmonary safety of CVT-301. Patients on standard levodopa regimen were randomized to CVT-301 or observational cohort. Pulmonary safety was assessed using spirometry and carbon monoxide diffusion capacity. There were no notable differences in pulmonary function compared with observational cohort. Exploratory efficacy assessments in the CVT-301 group support clinical efficacy.